Energy, environment, and quality in cement and construction industry. - Cement Manufacturers' Association (India); National Council for Cement and Building Materials (India) (National Council for Cement and Building Materials, 2002)
With reference to India; contributed articles presented at the seminar.
"Organized by the National Council for Cement and Building Materials (NCB), jointly with Cement Manufacturers' Association (CMA)"--Prelim. p. 9
Cover title.
Includes bibliographical references.
With reference to India; contributed articles presented at the seminar.
Keywords: Concrete construction / India / Congresses.; Concrete construction / C0ngresses.